Profitability Ratio Analysis at PT. Medikaloka Hermina, TBK - Miransyah, Giri Gintang; Dempo, Sri Rahayu Sangra; Sutisna, Sutisna (Bina Bangsa International Journal of Business and Management, 2021)
This study aims to determine the company's financial performance by using profitability ratio analysis, where the profitability ratio is a ratio that aims to determine the company's ability in generating profit over a certain period and also provides an overview of the level of management effectiveness in carrying out its operations. Profitability ratio consists of three ratios, among others Return On Assets, Return On Equity and Net Profit Margin. The research object is PT Medikaloka Hermina Tbk, where the health services company has done IPO (Initial Public Offering) or initial public offering so that economic growth of company very rapidly. The purpose of this study is to test and analyze the financial performance of the company at PT. Medikaloka Hermina Tbk. year 2018 - 2020 if reviewed from the profitability ratio. The sample of this research is financial reports from PT Medikaloka Hermina Tbk for 2018 – 2020 published on the Indonesia Stock Exchange website